Analisis Penggantian dan Biaya Perawatan Komponen Profibus dan Kontaktor pada Mesin Fine Blanking 1100 Ton di PT.XYZ - Adilogo, M maulana; Lokajaya, I Nyoman (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
It is necessary to do research to replace the profit bus and contactor components on a 110 ton Fine Blanking machine at PT. XYZ to analyze the cost and time needed to replace the profibus and contactor components. The aim of the research is to obtain the replacement time for profibus components and contactors, to obtain the cost and replacement time needed to replace profibus components and contactors. Through the distribution suitability test with the Kolmogorov Smirnov method, it was found that the time between failures of the profibus components corresponds to the Weibull distribution with an average replacement time of 29.54 days with a reliability of 47%. The contactor components are in accordance with the Weibull distribution with an average replacement time of 30.42 days with a reliability of 46%. The average repair time required for each profibus component replacement on a 1100 ton Fine Blanking machine is 3.85 minutes. Contactor on a 1100 ton Fine Blanking machine for 24.75 minutes. The cost required for each replacement of the Profibus component is IDR 1,250,000. For the contactor component on the 1100 ton Fine Blanking machine, IDR 650,000.